2021
DOI: 10.26855/er.2021.07.007
|View full text |Cite
|
Sign up to set email alerts
|

The Home-School Linkage Instructional System and Its Development Suggestions Under the Perspective of Large-Scale Home-Based Learning

Abstract: The learning ecosystem is the unified whole formed by education and its surrounding environment, including human elements such as the internal school education system and organization and non-human factors such as the external soft and challenging environment. However, the global COVID-19 outbreak in 2020 has led to large-scale home-based learning among students, which has broken the original ecological balance of learning. The interaction between the four elements of the traditional instructional system canno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 4 publications
1
5
0
Order By: Relevance
“…This agrees with Shang and Xing (2021), who observed that engaging students in discussions with parents about their studies enhances students' active knowledge acquisition, retention, and comprehension of the content. Parents'/Guardians'-students' Academic discussions allow students to elucidate concepts they do not understand and ensure a good understanding of all homework.…”
Section: Statementssupporting
confidence: 90%
“…This agrees with Shang and Xing (2021), who observed that engaging students in discussions with parents about their studies enhances students' active knowledge acquisition, retention, and comprehension of the content. Parents'/Guardians'-students' Academic discussions allow students to elucidate concepts they do not understand and ensure a good understanding of all homework.…”
Section: Statementssupporting
confidence: 90%
“…Class teachers can try to delegate some sections of the platform to parents for management, and set up themed discussion groups related to class management and student education. Parents serve as the administrators of the group and have active participants in these virtual spaces stand at the front desk of the event during regular parent meetings, fully playing a leading role [19]. (6) Realize the integration of the three educational elements of "parents, homeroom teachers, and students".…”
Section: Home School Communication Strategymentioning
confidence: 99%
“…Equaling 12, by far the greatest number of included articles that were returned, as evident from Table 1, were those that found self-directed learning, online learning, and mental health negative for public school students during COVID-19. These publications are on the following topics: learning in isolation [67]; High school student-athlete experiences [68]; Self-directed learning and attitude on online learning [69]; School connectedness still matters [70]; Implementation and challenges of online education [71]; Student evaluations of transitioned-online courses [72]; The impact of learning on science, social, and digital literacy [73]; A comparison of online learning challenges [74]; "Teachers act like we're robots" [75]; Socioeconomic inequality [76]; High school physical education teachers' perceptions [77]; and The home-school linkage [78].…”
Section: All Negativementioning
confidence: 99%